KAJIAN PERMASALAHAN SEDIMENTASI UNTUK OPTIMALISASI KEGIATAN PEMELIHARAAN DI WADUK SELOREJO - , Pandham Giri Sasangka, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Selorejo as one of yearly dam, at Pandansari village, Ngrantang sub-district, Malang regency, East Java province. The dam is located at Kali Konto river as Brantas river brance, at the join point with Kali Kwayangan, Â± 50 km western of Malang city, at an elevation of Â± 650 m above see level. The inlet water of the dam come from three mean streams, namely: Konto river, Pinjal river and Kwayangan river. The objectives of the study is, in general to determine of the sediment inlet of Selorejo dam, especially from three mean rivers as above mention and the effort to solving the problems. The study was conducted in four stages, there are: actual sedimentation analysis data of streams echosounding inlet to the dam using suspended load data